Antiretroviral therapy availability and equity of viral load testing for treatment follow-up at Eisleben Clinic, Limpopo Province - Mokgehle, Belinda Mokgadi (My University, 2023)
Background: Many studies have investigated patient-level causes of poor treatment outcomes, data on the effect of health systems on ART outcomes are scarce. Globally, ascending access to Human Immunodeficiency Virus (HIV) viral load testing for individuals living with HIV undergoing antiretroviral therapy in poor settings is a health priority. The global roll-out of HIV treatment has saved millions of lives: an estimated 16.5 million AIDS-related deaths have been averted since 2001. Literatures indicates that there has been a rapid scale up in the provision of Antiretroviral therapy (ART) in Sub Saharan Africa in the last decade with more than 7.5 million people receiving treatment by the end of 2012. In South Africa, HIV care is provided by both the private and public sectors. Notwithstanding that majority of public hospitals in South Africa have poor service delivery. The aim of the study is to determine Antiretroviral Therapy Availability and Equity of viral load testing for treatment follow-up at Eisleben clinic, Limpopo Province. Methodology: The study was qualitative in nature and used exploratory and descriptive design. The sampling of the study was purposive and involved nine (9) participants who met the criteria of the study: participants who are on antiretroviral therapy, 18years and above, both males and females. The study was conducted in Eisleben clinic, Capricorn district, Limpopo Province South Africa. Data collection was done through face to face interviews and analyzed using Thematic Content Analysis (TCA) to gain in-depth experience in the patients who are on treatment. Results and conclusion: The study found that barriers to access viral load testing were identified at all levels, health system, community level and patient level. This study shows that there is lack of sufficient knowledge on the factors that controls viral load suppression on patient who are taking ART. Some highlighted that the clinicians who are offering the treatment in the clinics need to explain and teach them to increase knowledge of the factors that controls the viral load suppression. It has been observed that shortage of staff in Eisleben clinic contributes to lack of health education to inform the patients about their health status. Amongst adult patients in the region, various barriers to ART adherence have been identified: fear of HIV status disclosure, HIV-related stigma, alcohol use and drug abuse, forgetfulness, complicated ART regimens, pill burden, side effects, transportation costs, and financial constraints.
Thesis (MPH.) -- University of Limpopo, 2023
Keywords: HIV treatment; HIV viral load; Antiretroviral therapy; HIV testing; Highly active antiretroviral therapy; HIV infections -- Treatment; HIV-positive persons -- Care -- South Africa; HIV-positive persons; Nevirapine